Family presence during resuscitation: patient and family members’ preferences and attitudes - Pratiwi, Indah D. (International Journal of Research in Medical Sciences, 2018)
Background: This literature review presents a review of the available studies into family presence during resuscitation (FPDR) in the context of emergency department and critical care unit from the point of view of patients and family members. This literature review provides the background for understanding the debate about FPDR. The paper examines the state of current research on the topic and points out gaps in existing literature. Methods: A comprehensive search of OVID Nursing, Web of Science (Web of Knowledge), Elsevier, ProQuest and Google Scholar electronic search engine. Thematic analysis was used to extract themes from the 25 studies reviewed (quantitative, qualitative and mixed-methods studies), resulted in five major themes and five minor themes. Results: Five major themes from this literature review were: (1) patient and family members’ preferences; (2) perceived benefits of family presence during resuscitation; (3) perceiving family presence as a right; (4) the importance of a family facilitator; and (5) the involvement of decision making. Conclusions: This literature review has established the potentials of family presence during resuscitation to improve patient and family-centred care by helping and providing family members to manage and to adjust during traumatic circumstances.